Proteomic analysis of endoscopically (ePFT) collected gastroduodenal fluid using in-gel tryptic digestion followed by liquid chromatography-tandem mass spectrometry - Paulo, Joao A. (2010)
PURPOSE: Proteomic analysis of gastroduodenal fluid offers an alternative strategy to study diseases, such as peptic ulcer disease and gastric cancer. We use in-gel digestion followed by liquid chromatography-tandem mass spectrometry (GeLC-MS/MS) to profile the proteome of gastroduodenal fluid collected during the endoscopic function test (ePFT). EXPERIMENTAL DESIGN: Gastroduodenal fluid specimens collected during ePFT from six patients with upper abdominal pain were subjected to proteomic analysis. We extracted proteins using three chemical precipitation reagents (acetone, ethanol, and trichloroacetic acid) and analyzed each sample by SDS-PAGE and GeLC-MS/MS for protein identification. Cellular origin and molecular function of the identified proteins were determined via gene ontology analysis. RESULTS: All three precipitation techniques successfully extracted protein from gastroduodenal fluid, with acetone resulting in excellent resolution and minimal protein degradation compared to the other methods. A total of 134 unique proteins were found in our GeLC-MS/MS analysis of ePFT-collected gastroduodenal fluid samples. Sixty-seven proteins were identified in at least two of the three samples. Gene ontology analysis classified these proteins mainly as being peptidases and localized extracellularly. CONCLUSIONS: ePFT, followed by acetone precipitation, and coupled with LC-MS/MS, can be used to safely collect gastroduodenal fluid from the upper gastrointestinal tract for mass-spectrometry-based proteomic analysis.